2004
DOI: 10.3766/jaaa.15.5.3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Laboratory Measures of Directional Advantage and Everyday Success with Directional Microphone Hearing Aids

Abstract: The improvement in speech recognition in noise obtained with directional microphones compared to omnidirectional microphones is referred to as the directional advantage. Laboratory studies have revealed substantial differences in the magnitude of the directional advantage across hearing-impaired listeners. This investigation examined whether persons who were successful users of directional microphone hearing aids in everyday living tended to obtain a larger directional advantage in the test booth than persons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 18 publications
3
72
1
Order By: Relevance
“…This is true mainly because of the short reverberation times that are typical of audiometric sound rooms. These conclusions confirm those of Cord et al (2004). A related point is that the audiometric sound room, with its negligible RT (.05 sec), appears to be a poor model for predicting listener preference in everyday listening environments.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…This is true mainly because of the short reverberation times that are typical of audiometric sound rooms. These conclusions confirm those of Cord et al (2004). A related point is that the audiometric sound room, with its negligible RT (.05 sec), appears to be a poor model for predicting listener preference in everyday listening environments.…”
Section: Resultssupporting
confidence: 86%
“…Amlani, 2001;Boymans & Dreschler, 2000;Cord et al, 2004;Nielsen, 1973;Nielsen & Ludvigsen, 1978;Preves et al, 1999;Valente et al, 1995). Among studies that have assessed directional advantage under real-world conditions, some have reported a perceived functional advantage (Nielsen, 1973;Chasin, 1994: Preves et al, 1999, while other studies have not (Mueller et al, 1983;Kuk, 1996;Walden et al, 2000;Cord et al, 2002Cord et al, , 2004. In part, these negative outcomes may reflect the fact that listeners have a tendency to use exclusively the default mode, often omnidirectional, after being fitted with switchable omnidirectional/directional hearing aids.…”
Section: Sumariomentioning
confidence: 91%
See 1 more Smart Citation
“…A caution in interpreting the results is that improvements due to directional microphones obtained in the laboratories may not always translate to higher perceived speech intelligibility or preference ratings in real-world environments (Mueller et al, 1983;Walden et al, 2000;Cord et al, 2002Cord et al, , 2004Surr et al, 2002;Ricketts et al, 2003;Spriet et al, 2007). The discrepancy can be attributed to reverberation and/or critical distance in the listening environments, relative locations of the signal and noise, the type and/or location of noise encountered, the percentage of time the use of directional microphone is needed (see Chung (2004) for a detailed review).…”
Section: Discussionmentioning
confidence: 96%
“…By focusing on these common features, it is expected that study findings are salient to the highest number of hearing aid dispensing audiologists. In addition, numerous research studies have demonstrated benefits of dispensing three of these features (e.g., directional processing, Cord, Surr, Walden, & Dyrlund, 2004;Killion, 2004;Kochkin, 2003;Ricketts & Henry, 2002;Ricketts, Henry, & Gnewikow, 2003;Ricketts & Hornsby, 2003;Ricketts, Hornsby, and Johnson, 2005;Walden, Surr, Cord, & Dyrland, 2004; digital feedback suppression processing, Chung, 2004;Freed & Soli, 2006;Greenberg, Zurek, & Brantley, 2000;E. E. Johnson, Ricketts, & Hornsby, 2007;Kates, 1999;Kiessling, Brenner, Jespersen, Groth, & Jensen, 2005; and the telecoil, Pettersson, 1987;Stoker, French, & Lyons, 1986).…”
Section: Rationale For the Selection Of Product Features Examined Formentioning
confidence: 99%